2013
DOI: 10.1002/chem.201300554
|View full text |Cite
|
Sign up to set email alerts
|

Substrate‐Dependent Stereospecificity of Tyl‐KR1: An Isolated Polyketide Synthase Ketoreductase Domain from Streptomyces fradiae

Abstract: The stereospecificity of an enzymatic reaction depends on the way in which a substrate and its enantiomer bind to the active site. These binding modes cannot be easily predicted. We have studied the stereospecificity and stereoselectivity of the ketoreductase domain Tyl-KR1 of the tylactone polyketide synthase from Streptomyces fradiae by analysing the stereochemical outcome of the reduction of five different keto ester substrates. The absolute configuration of the Tyl-KR1 reduction products was determined by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
42
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 40 publications
3
42
0
Order By: Relevance
“…One such example is reported by Häckh in the reduction of 2-Me-3-oxo esters (Scheme 3). [28] Replacement of an SNAC ester with an ethyl ester increased enantioselectivity from 43% ee to 92% ee. Interestingly, the same ester substitution for 2-Me-3-oxovalerate esters reversed the stereochemical course of the reduction from (2 R ,3 R ) to (2 S ,3 S ).…”
Section: β-Keto Ester Reductionmentioning
confidence: 99%
“…One such example is reported by Häckh in the reduction of 2-Me-3-oxo esters (Scheme 3). [28] Replacement of an SNAC ester with an ethyl ester increased enantioselectivity from 43% ee to 92% ee. Interestingly, the same ester substitution for 2-Me-3-oxovalerate esters reversed the stereochemical course of the reduction from (2 R ,3 R ) to (2 S ,3 S ).…”
Section: β-Keto Ester Reductionmentioning
confidence: 99%
“…7 In contrast, studies in which the 1 st KR from the tylosin PKS (TylKR1) was incubated with 2-methyl-3-oxopentanoyl diketides linked to handles through an oxo-ester showed that reversals in stereocontrol can result from unnatural handles. 10 To further dissect the interactions that mediate KR stereocontrol, we varied the chemistry and size of the handles of 2-methyl-3-oxopentanoyl substrates and evaluated the effects in structure-activity relationship (SAR) fashion.…”
mentioning
confidence: 99%
“…To appreciate the extent to which PksKR1 is specialized in performing its role as a stereospecific α‐KR, we incubated the α‐keto substrate 2 with the biocatalytically robust cis ‐AT KR enzymes TylKR1 and EryKR1 [Fig. (b)] . EryKR1 was able to perform the stereospecific reduction of 2 to yield a product that has a mass consistent with the D‐α‐hydroxy reduction product.…”
Section: Resultsmentioning
confidence: 99%